2023
DOI: 10.1186/s13613-023-01135-8
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Critical Care Society clinical practice guidelines on the prevention of venous thromboembolism in adults with trauma: reviewed for evidence-based integrity and endorsed by the Scandinavian Society of Anaesthesiology and Intensive Care Medicine

Marwa Amer,
Mohammed S. Alshahrani,
Yaseen M. Arabi
et al.

Abstract: Background To develop evidence-based clinical practice guidelines on venous thromboembolism (VTE) prevention in adults with trauma in inpatient settings. Methods The Saudi Critical Care Society (SCCS) sponsored guidelines development and included 22 multidisciplinary panel members who completed conflict-of-interest forms. The panel developed and answered structured guidelines questions. For each question, the literature was searched for relevant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 114 publications
(244 reference statements)
0
4
0
Order By: Relevance
“…Guidelines for thrombosis prophylaxis in critically ill trauma patients typically recommend the administration of subcutaneous low-molecular-weight heparin (LMWH) or unfractionated heparin (UFH) [10][11][12][13]. The timing of initiation is tailored to each patient, but pharmacologic prophylaxis should typically be started within 24-72 h posttrauma in the absence of ongoing bleeding.…”
Section: Currently Recommended Thrombosis Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines for thrombosis prophylaxis in critically ill trauma patients typically recommend the administration of subcutaneous low-molecular-weight heparin (LMWH) or unfractionated heparin (UFH) [10][11][12][13]. The timing of initiation is tailored to each patient, but pharmacologic prophylaxis should typically be started within 24-72 h posttrauma in the absence of ongoing bleeding.…”
Section: Currently Recommended Thrombosis Prophylaxismentioning
confidence: 99%
“…The pharmacologic thrombosis prophylaxis strategies currently in practice involve administering dalteparin, enoxaparin, and UFH in standardised doses [12,13]. However, the application of these one-size-fits-all doses, especially given the subcutaneous route of administration, presents challenges.…”
Section: Currently Recommended Thrombosis Prophylaxismentioning
confidence: 99%
“…Evidence also suggests that UFH and LMWH can reduce cerebral edema and improve neurological recovery by inhibiting the recruitment of leukocytes [29,30] . For the prevention of VTE events, most experts and studies prefer LMWH over UFH, as LMWH has a similar risk of bleeding but a lower incidence of DVT and is associated with reduced mortality [31][32][33][34] .…”
Section: Tbi and Prophylactic Anticoagulation Therapymentioning
confidence: 99%
“…The efficacy of pharmacological prophylaxis in preventing thromboembolic events after TBI is well established in the updated Brain Trauma Foundation guideline [67]. In a recent SR [104] and GL [105], the authors concluded that low-molecular-weight heparin (LMWH) or UFH can be safely administered as early as 24-48 h post-injury for patients with low-hemorrhagic-risk TBI and stable pictures upon repeated imaging. However, TBI patients receiving OAT were excluded from the selected studies.…”
Section: Prophylaxis and Anticoagulant Resumption After Tbimentioning
confidence: 99%